(untitled) (Experimental biology, 2015)
In this article we give the results lactic acid bacteria have the ability to interact with ions of heavy metals. We used method of qualitative reaction which shows lactic acid bacteria’s ability to absorb lead and cadmium ions on. 125 strains of lactic acid bacteria isolated from camel milk and shubat were tested.